The mitochondrial‐derived peptide MOTS‐c is a regulator of plasma metabolites and enhances insulin sensitivity - Kim, Su‐Jeong (Physiol Rep, 2019)
MOTS‐c is an exercise mimetic and improves insulin sensitivity in aged and diet‐induced obese mice. Although plasma markers are good markers for the metabolic condition, whether MOTS‐c changes plasma markers in diet‐induced obese mice has not been examined. Here, we used an unbiased metabolomics approach to examine the effect of MOTS‐c on plasma markers of metabolic dysfunction. We found that three pathways – sphingolipid metabolism, monoacylglycerol metabolism, and dicarboxylate metabolism – were reduced in MOTS‐c–injected mice. Interestingly, these pathways are upregulated in obese and T2D models. MOTS‐c improves insulin sensitivity and increases beta‐oxidation to prevent fat accumulation in DIO mice through these pathways. These results provide us a better understanding of the mechanism of how MOTS‐c improves insulin sensitivity and reduces the body weight and fatty liver and opens a new venue for further study.